Faktor-Faktor Yang Mempengaruhi Remaja Menggunakan Narkoba di Desa Surbakti Kecamatan Simpang Empat Kabupaten Karo Tahun 2022 - Herianto Bangun (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Drugs are substances that can have certain effects on those who use them by inserting the drug into their bodies. This research aims to look at the factors that influence teenagers using drugs in Surbakti Village, Simpang Empat District, Karo Regency in 2022. The type of research used in this research is quantitative analytical with a cross sectional approach method where the sample is 30 respondents using simple random sampling techniques and the type of data used is primary data obtained directly from respondents and secondary data taken from the Village head's office. Based on the research results obtained, the chi-square statistical test results based on environment obtained p=0.977, namely there is no relationship between the environment and teenagers who use drugs. Based on personality, it was obtained that p=0.084, namely there is a relationship between personality and teenagers who use drugs. Based on family, it was found that p=0.163, namely there was no relationship between family and teenagers who used drugs. Based on education, it was found that p=0.104, namely there is a relationship between education and teenagers who use drugs. This means that p is smaller than the value of a (0.05) and thus Ho is accepted and Ha is rejected, which means there is no relationship between environment, personality, family and education and teenagers who use drugs.